2021
DOI: 10.1111/jdv.17319
|View full text |Cite
|
Sign up to set email alerts
|

Cerebriform sebaceous nevus: a subtype of organoid nevus due to specific postzygotic FGFR2 mutations

Abstract: Background Postzygotic mutations in FGFR2 have been identified in mosaic forms of acne, keratinocytic epidermal nevi, nevoid acanthosis nigricans / rounded and velvety epidermal nevus and in two fetuses with papillomatous pedunculated sebaceous nevus (PPSN). Objectives To determine the clinical and genetic characteristics of children with cerebriform, papillomatous and pedunculated variants of sebaceous nevi. Methods Infants diagnosed with sebaceous nevi characterized by a cerebriform, papillomatous and/or ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In addition, the same mutation has been identified in 5 cases of cerebriform sebaceous nevus on the scalp and none of these children had neurological issues. 5 We found no other cases of RAVEN associated with autism, although it has been suggested that neuronal growth regulator 1 and FGFR2 cooperatively regulate cortical development and core behaviors related to autism in mice. 6 In conclusion, we present a case of RAVEN caused by a heterozygous mutation in FGFR2.The role of the FGFR2 mutation in autism should be further evaluated in this patient.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, the same mutation has been identified in 5 cases of cerebriform sebaceous nevus on the scalp and none of these children had neurological issues. 5 We found no other cases of RAVEN associated with autism, although it has been suggested that neuronal growth regulator 1 and FGFR2 cooperatively regulate cortical development and core behaviors related to autism in mice. 6 In conclusion, we present a case of RAVEN caused by a heterozygous mutation in FGFR2.The role of the FGFR2 mutation in autism should be further evaluated in this patient.…”
Section: Discussionmentioning
confidence: 56%
“…Tanaka 4 et al presented a case of congenital extensive linear keratinocytic epidermal nevi of the trunk and acral skin caused by a somatic FGFR2 p.Cys382Arg mutation, the same mutation identified in our patient. In addition, the same mutation has been identified in five cases of cerebriform sebaceous nevus on the scalp and none of these children had neurological issues 5 …”
Section: Discussionmentioning
confidence: 76%
“…One NRAS mutation (Q61R) was found, marking the first causative NRAS mutation in NSS [5], as well as unique mutations such as in the PRKRIR gene (A1674T, R558S) for one patient, and a mutation in the RRP7A gene (C670T, R224W) in another [27]. Theiler et al [6], examined cerebriform, papillomatous, and/or pedunculated sebaceous nevi from eight pediatric patients. In six of eight nevi, a mutation was found in the FGFR2 transmembrane domain mutation (either C382R or V395D) [6].…”
Section: /6 Mutational Analysismentioning
confidence: 99%
“…Theiler et al [6], examined cerebriform, papillomatous, and/or pedunculated sebaceous nevi from eight pediatric patients. In six of eight nevi, a mutation was found in the FGFR2 transmembrane domain mutation (either C382R or V395D) [6]. For a patient with FGFR3-ENS (Garcia-Hafner-Happle syndrome), two FGFR3 mutations were identified -R248C [7] and S249C [42].…”
Section: /6 Mutational Analysismentioning
confidence: 99%
“…NS is susceptible to hormone-mediated changes during puberty and can develop secondary neoplasms in adulthood. Management for NS has evolved over the years, now typically favoring clinical observation in infancy and early childhood, followed by complete excision during adolescence before puberty [1][2][3][4][5][6][7]. If multiple lesions are present and/or a single lesion is very large in size, NS may be associated with certain syndromes, such as Schimmelpenning syndrome or phakomatosis pigmentokeratotica, both of which can present with extracutaneous defects [5].…”
Section: Introductionmentioning
confidence: 99%